MICROBIOLOGICAL AND NUTRITIONAL EVALUATION OF FLOURS MADE FROM TURIAÇU PINEAPPLE PEELS FOR FOOD PURPOSES (REMUNOM, 2024)
Brazil has become one of the largest fruit producers in the world. However, this great productivity generates a significant amount of agro-industrial waste, which has a high nutritional load of vitamins, minerals, fibers and phenols, but which is discarded incorrectly without any prior treatment in the environment, contributing to urban pollution. In this context, the main objective of this work was to add value to an agro-industrial residue, producing flours from the peels of the pineapples of Turiaçu variety, evaluating them with microbiological analysis (yeasts and molds), their nutritional potential [moisture; fixed mineral residue; lipids; proteins; carbohydrates and caloric value] in addition to shelf life (pH and titratable acidity), aiming for possible applications in food formulations. The fruits were purchased at the Supply Center (CEASA) in the city of São Luís - MA. After being sanitized, their peels were dried in a fruit dehydrator at 60°C for 90 hours. They were then crushed and sieved to obtain the flours (FCA). The microbiological quality of the flours was considered good, with a mold and yeast count of 2.2 x 103 CFU/g, a value lower than the limit established by Brazilian legislation. Regarding nutritional analyses, the following results were obtained: humidity (6.16%); fixed mineral residue (ash) (4.77%), lipids (1.26%), proteins (4.40%), carbohydrates (83.41%) and caloric value (364.29 kcal.100 g-1), all these values corroborate the standards established by Brazilian legislation (MAPA) and are similar to the results available in the scientific literature. For shelf test analyses (pH and titratable acidity) within a six-month monitoring interval, the flour proved to be safe for handling during this period, without there being a risk of microbial attack, as they were still within the range of acidity (pH < 4.5). The results obtained demonstrated that Turiaçu pineapple peel flour has great technological potential in the development of new food products, and can be included in the diet of children, young people and adults, in addition to reducing environmental problems with excess waste.